An Investigation of students' early pregnancy, causes and effects.: Dodoma District - SHILLINDE, AHMED MIKE (International Journal For Research In Educational Studies, 2024)
Adolescent pregnancy is a global catastrophe that has recently emerged as a health issue and has a significant negative impact on the socioeconomic well-being of nations, cultures, and families. Parents, school officials, and other stakeholders have expressed serious concerns about students’ pregnancy which is defined as an instance of a girls’ student becoming pregnant between the ages of thirteen (13) and nineteen (19). The study aimed to find out the causes and consequences of students’ pregnancy in Jamuhuri and City secondary schools in the Dodoma Region. For this study, a descriptive research design was chosen. The research was guided by three research questions. The researchers created a tool called "Students Early Pregnancy in Secondary School’" to be used in gathering data. Experts validated the instrument, and test reliability was established. The Research Questions were addressed using mean statistics. The study's conclusions demonstrate that several factors, including the absence of comprehensive sex education, cultural and religious beliefs, insufficient support from schools, lack of adequate role models in the field of education, socioeconomic factors, stigma and taboos, peer pressure, the role played by the media, parenting lifestyle, poor using contraception, and financial circumstances, can contribute to student early pregnancy. The study also found that building hostels and girls’ clubs, education for both parents and students, punishment for those impregnating students, and good relationships between parents and teachers are effective ways to reduce students’ pregnancy among secondary school students. Other effects of students’ early pregnancy include dropping out of school, health problems, isolation, and rejection by parents and peers. This study will assist teachers, students, and parents to work together and strengthen their cooperation toward their student's achievement at the schools.